Further Evidence for Pre-metamorphosis Larval Eye Reduction in the Holometabola (Insecta: Mecoptera: Panorpa vulgaris Imhoff & Labram, 1836). - Saltin, Brian D. (Contributions to Entomology = Beiträge zur Entomologie, 2015)
Larvae of Panorpa are eye developmentally unusual. They possess a multi-lense complex-eye-like visual organ, which was found not to be part of the later adult eye. A highly significant deviation in the ommatidia number during the larval stages was found, with instar 3 (of 4) having most ommatidia. Keywords Eye, Mecoptera, Panorpa, Metamorphosis, Development.